Brokered Marriage Administration: Rational Strategies of Muslim Communities in Navigating the Bureaucratization of Marriage in Indonesia - Umairoh, Putri; Hakimah, Nur; Utsany, Royan; Muala, Asyharul (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
Indonesian law requires Muslim marriages to be formally registered to obtain state recognition. However, in practice, the marriage registration process is often bureaucratic and complex, limiting couples’ ability to fulfill administrative requirements independently. In response to these challenges, some Muslim couples delegate marriage administration to third parties who are socially recognized as marriage administration brokers. This article examines the delegation of marriage administration as a rational strategy employed by Muslim couples to navigate the bureaucratic complexities of marriage registration. Using a socio-legal approach grounded in field-based research, the study analyzes empirical data through the lens of James S. Coleman’s rational choice theory. The findings demonstrate that the delegation of marriage administration is driven by the convergence of three key factors: the structural complexity of state bureaucracy, couples’ cognitive and temporal limitations, and strong social capital that legitimizes marriage brokers as trusted intermediaries. Furthermore, the study shows that reliance on brokers cannot be attributed solely to economic considerations, as relatively high brokerage fees are perceived as rational compensation for time efficiency, reduced administrative risk, and the attainment of legal certainty. This article argues that marriage administration brokers function as informal social institutions mediating relations between Muslim communities and the state in confronting the bureaucratization of Islamic family law in Indonesia. [Hukum nasional Indonesia mewajibkan setiap perkawinan Muslim untuk dicatatkan guna memperoleh pengakuan hukum dari negara. Namun, dalam praktiknya, proses pencatatan perkawinan kerap dihadapkan pada kompleksitas birokratis yang membatasi kapasitas pasangan untuk memenuhi persyaratan administratif secara mandiri. Sebagai respons terhadap kondisi tersebut, sebagian pasangan Muslim mendelegasikan pengurusan administrasi perkawinan kepada pihak ketiga yang secara sosial dikenal sebagai makelar administrasi perkawinan. Artikel ini bertujuan untuk menganalisis praktik pelimpahan administrasi perkawinan sebagai strategi rasional yang digunakan oleh pasangan Muslim dalam menavigasi kerumitan birokrasi pencatatan perkawinan. Penelitian ini menggunakan pendekatan sosio-legal berbasis studi lapangan, dengan analisis data yang dilakukan menggunakan teori pilihan rasional dari James S. Coleman. Temuan penelitian menunjukkan bahwa praktik delegasi administrasi perkawinan didorong oleh pertemuan tiga faktor utama, yaitu kompleksitas struktural birokrasi negara, keterbatasan kognitif dan temporal pasangan, serta kuatnya modal sosial yang membangun legitimasi makelar sebagai perantara yang dipercaya. Studi ini juga menegaskan bahwa penggunaan jasa makelar tidak dapat direduksi pada pertimbangan ekonomi semata, mengingat biaya jasa yang relatif tinggi justru dipersepsikan sebagai kompensasi rasional atas efisiensi waktu, pengurangan risiko administratif, dan perolehan kepastian hukum. Artikel ini berargumen bahwa makelar administrasi perkawinan berfungsi sebagai institusi sosial informal yang memediasi relasi antara masyarakat Muslim dan negara dalam menghadapi kompleksitas birokratisasi hukum keluarga Islam di Indonesia.]